Pengaruh Keselamatan dan Kesehatan Kerja Terhadap Kinerja Karyawan PT PP Presisi, Tbk Proyek Tol Manado-Bitung - Kourouw, Pemsi; Tatimu, Ventje; Sambul, Sofia A. P. (Sam Ratulangi University, 2019)
This study aims to determine the effect of Occupational Safety and Health on Employees Performance at PT. PP Presisi.Tbk Proyek Tol Manado-Bitung. This study uses a quantitative approach, with a sample of 70 respondents. The sampling techniques in this study were to use Simple Random Sampling. Data collection techniques in this study are by using a questionnaire distribution. The analysis techniques used in this study includes validity test, reliability test, multiple regression test, F test, t-test and coefficient of determination. The data that has fulfilled the analysis techniques was processed using the help of the SPSS 25 program. It can be seen from the results of the statistical test that the Occupational Safety and Health independent variables affect the dependent variable of Employee Performance. The results showed that based on the calculation of the coefficient of determination the influence of the independent variable Occupational Safety and Health on the dependent variable of Employee Performance is 0,368 or 3,68 % which shows that Employee Performance can be influenced by Occupational Safety variable and Occupational Health variable. While the remaining 63, 2 % is influenced by other variables that do not exist in this study. This shows that Occupational Safety and Health has a significant effect on Employee Performance. Where if Occupational Safety is guaranteed and Occupational Health is goodwill improve Employee Performance.